Pengaruh Harga Jual dan Produksi Tandan Buah Segar (TBS) terhadap Upah Buruh Kelapa Sawit di Desa Meranti Kecamatan Bilah Hulu Kabupaten Labuhanbatu - Lia Nur Fatmawati; Marliyah Marliyah; Laylan Syafina (Universitas 45 Surabaya, 2024)
This research aims to determine the effect of selling prices and production of fresh fruit bunches (FFB) on the wages of oil palm workers in Meranti Village, Bilah Hulu District, Labuhanbatu Regency. The research data used in this research is primary data obtained directly from the first source, either from individuals, such as the results of filling out questionnaires and distributed to oil palm farm workers in Meranti Village, Bilah Hulu District, Labuhanbatu Regency. The method used is multiple linear regression analysis assisted by SPSS (Statistical Package For Social Science) 2020 software. The results of the research conducted show that the selling price has a negative effect on the wages of oil palm workers in Meranti Village, Bilah Hulu District. FFB production has a positive and significant effect on the wages of palm oil workers in Meranti Village, Bilah Hulu District, Labuhanbatu Regency. The selling price and production of FFB simultaneously and significantly influence the wages of palm oil workers in Meranti Village, Bilah Hulu District, Labuhanbatu Regency.